The Role of Social Media in the 2024 Indonesian Election Campaign: Regulatory Challenges and Global Political Influence - Zayyin Abdul; Zahirah, Zalfa (Mandala: Jurnal Ilmu Hubungan Internasional, 2023)
Social media has become a significantly influential platform in the modern political process in many countries, including Indonesia. As Indonesia approaches the 2024 General Election (Pemilu), the role and impact of social media in political campaigns are increasingly under scrutiny. Despite the advantages social media offers in influencing public opinion and political participation, challenges such as the spread of hoaxes and hate speech also emerge. Recent studies have explored the perceptions of voters, particularly the younger generation, regarding social media in the political context. Therefore, the aim of this research is to provide in-depth insights into the role of social media in Indonesian politics, formulate policy recommendations to enhance democratic integrity, and explore the impact of social media in the 2024 General Election. It is hoped that this study will contribute significantly to understanding the modern political dynamics and the role of social media in the digital era.